2014
DOI: 10.1002/adfm.201303796
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Doping and Tuning of the Work Function and Dirac Point in Graphene Using Photoacid and Photobase Generators

Abstract: This work demonstrates that photochemical doping of CVD-grown graphene can be easily achieved using photoacid (PAG) and photobase (PBG) generators such as triphenylsulfonium perfl uoro-1-butanesufonate (TPS-Nf ) and 2-nitrobenzyl N -cyclohexylcarbamate (NBC). The TPS-Nf ionic onium salt photoacid generator does not noticeably dope or alter the electrical properties of graphene when coated onto the graphene surface, but is very effective at inducing p-doping of graphene upon exposure of the PAG-coated graphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 66 publications
0
20
0
1
Order By: Relevance
“…The most common ionic PAGs are onium salt derivatives. Although onium salts have been known for a century, their application in photopolymerization has only been recently developed . When onium salts are exposed to light, photolysis occurs, which gives rise to the simultaneous formation of Brønsted acids and cations.…”
Section: Photoacid Generatorsmentioning
confidence: 99%
“…The most common ionic PAGs are onium salt derivatives. Although onium salts have been known for a century, their application in photopolymerization has only been recently developed . When onium salts are exposed to light, photolysis occurs, which gives rise to the simultaneous formation of Brønsted acids and cations.…”
Section: Photoacid Generatorsmentioning
confidence: 99%
“…[23][24][25][26] Further, lithography typically involves the use of solvents and chemicals that might affect or degrade the properties of doped graphene. [8][9][10][11]21,[27][28][29][30][31] Here, we show that all of these challenges for efficient graphene-based TCEs can be effectively addressed at once via a thin (>10 nm) metal oxide (MoO 3 or WO 3 ) coating of the graphene. The metal oxide can be deposited by various means, 9,18,19 but we focus here on thermal evaporation.…”
mentioning
confidence: 99%
“…Manipulating the properties of graphene without degrading its electrical properties is highly desired to realize a wide range of applications of graphene. Previous studies have reported various dopants for graphene; [32][33][34][35][36] however, there still remain a few challenges on developing dopants that can be processed and patterned easily. Our solution-processable p-type dopant has the potential to manipulate the electrical properties of graphene, which we demonstrate for gas sensing applications.…”
Section: Resultsmentioning
confidence: 99%